2016
DOI: 10.1016/j.jped.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Critical assessment of the pH of children's soap

Abstract: Knowledge of the pH of children's soap by doctors and users is important, considering the great pH variability found in this study. Moreover, liquid soaps, and especially syndets, are the most recommended for the sensitive skin of neonates and infants, in order to guarantee skin barrier efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
3
18
0
2
Order By: Relevance
“…Although all products were formulated in accordance with contemporary design strategies for mild cleansing products, their pH values were 7 and higher (as high as 9.85-12.35) for all except two products, one with pH of 3.6 and one with pH 5.5, which were associated with the lowest irritation index. Another, more recent study investigated a pH of 67 children's soaps and showed that the pH of the assessed soaps ranged from 4.4 to 11.5, with 11% of soaps with a pH < 5.9 and only two products with information about pH labeled on the product [110]. An additional survey made by Tarun et al showed that soaps and shampoos commonly used by the Indian population have a pH of 9-10 (soaps) and 6-7 (shampoos), and thus, they can be considered as not ideal, especially for patients with sensitive or acne-prone skin [111].…”
Section: Cleansersmentioning
confidence: 99%
“…Although all products were formulated in accordance with contemporary design strategies for mild cleansing products, their pH values were 7 and higher (as high as 9.85-12.35) for all except two products, one with pH of 3.6 and one with pH 5.5, which were associated with the lowest irritation index. Another, more recent study investigated a pH of 67 children's soaps and showed that the pH of the assessed soaps ranged from 4.4 to 11.5, with 11% of soaps with a pH < 5.9 and only two products with information about pH labeled on the product [110]. An additional survey made by Tarun et al showed that soaps and shampoos commonly used by the Indian population have a pH of 9-10 (soaps) and 6-7 (shampoos), and thus, they can be considered as not ideal, especially for patients with sensitive or acne-prone skin [111].…”
Section: Cleansersmentioning
confidence: 99%
“…Em consequência disto, o manto ácido não consegue desenvolver sua função bacteriostática, permitindo ação de agentes patógenos, o que reforça a necessidade de inserir um sabão que apresente pH ácido. (11,19) Quanto ao pH do sabão utilizado, apesar de a maioria dos profissionais estudados utilizarem sabão neutro, a literatura científica indica o pH deve ser levemente ácido. Considerando a maturidade da pele do RN, o uso de produtos com o pH baixo (5,5) pode ajudar a desenvolver mais rapidamente o estrato córneo e o manto ácido do RN, pois, como citado, ela é essencial para a proteção contra agentes penetrantes exógenos, agentes infecciosos e para a manutenção da função imunológica inata.…”
Section: Discussionunclassified
“…Many studies have suggested that topical products should be acidified, with pH values ranging from 4 to 6. Side effects such as skin irritation, damaged skin barrier, and cytotoxicity have been documented when using high pH topical products 68 . The skin's buffering ability is a one‐of‐a‐kind natural mechanism that helps it resist acid/alkaline aggression 69 .…”
Section: Future Directions and Prospectsmentioning
confidence: 99%
“…Side effects such as skin irritation, damaged skin barrier, and cytotoxicity have been documented when using high pH topical products. 68 The skin's buffering ability is a one-of-a-kind natural mechanism that helps it resist acid/alkaline aggression. 69 With the pH of pectin that is commonly reported to be slightly in the acidic region, 70 therefore the nanoformulations appear best suited to be further explored for use in percutaneous delivery.…”
Section: Future Directions and Prospectsmentioning
confidence: 99%